“We don’t have a box”: Understanding Hidden Disability Identity Utilizing Narrative Research Methodology - Aimee Valeras (Disability Studies Quarterly, 2010)
A "hidden disability," one unapparent to outside observers, defies the outward social construction of disability. A narrative research approach is used to understand the process of personal identification (or lack thereof) with being "disabled." Self-narratives were elicited from three men and three women, ranging in age from 21 to 53 years who have had a hidden physical disability since before age thirteen. The conditions represented are: Juvenile Diabetes, Asthma, Juvenile Rheumatoid Arthritis, Epilepsy, Muscular Dystrophy, and Celiac Disease. While persons with hidden disabilities are afforded a sense of anonymity, they must contend with different challenges, including learning strategic self-disclosure and impression management; when to disclose and make disability visible and when to "pass" and give society the impression of "able-bodiedness." The choice, to be or not to be disabled, has important implications for the way we conceptualize disability, and the concept of identity as a whole.